The maximal standardized uptake value is a predictive factor of pelvic lymph node involvement in patients with early stage cervical carcinoma - Wiśniewski, Tomasz; Terlikiewicz, Joanna; Lebioda, Andrzej; Makarewicz, Roman; Małkowski, Bogdan; Ziółkowska, Ewa (Contemporary Oncology/Współczesna Onkologia, 2010)
Aim of the study: The aim of this study was to assess the contribution of positron emission tomography (PET) scanning in the staging of cervical cancer. Material and methods: 27 patients with carcinoma of the cervix in stage Ib1 (23 pts) and IIa (4 pts) according to the FIGO classification were involved in this retrospective review. They had an 18-fluorodeoxyglucose PET scan as part of the staging before the planned treatment. All of them had preoperative brachytherapy, and surgical treatment with histological verification of pelvic nodules was performed in 25 patients. The value of SUVmax was defined for all suspected areas in the images from the PET-CT scanner. A logistic regression model was used to connect SUVmax with the risk of regional lymph node involvement. Results: The PET CT scanning detected the tumour volume in 26 cases of cervical carcinoma and lymph node involvement was recognized in 2 patients. However, this examination did not show the occurrence of microscopic metastases in the pathological examination in 4 patients. A statistically significant correlation between the value of maximum SUV and the risk of nodal metastases was found. An increase of SUVmax by 1 unit increased the risk of lymph node disease by a mean of 6.3% (95% CI: 2.4-10.3%). Conclusions: The PET-CT is a useful diagnostic tool in staging cervical carcinoma, especially to detect extrapelvic metastases. SUVmax is a value that strongly correlates with pelvic lymph node status in early-stage cervical carcinoma.